Efficiency of Using NPK Fertilizer with Vermicompost Addition to Growth and Results of Soybean Plants - M. Arifin; P. Sukaryorini; T. Mujoko (Future Science)
The continued use of chemical fertilizers and pesticides on agricultural land, causing damage to land which results in degradation of land productivity. Organic agriculture is a green revolution movement that reduces agricultural inputs in the form of the use of organic fertilizers and pesticides, by using local natural resources in a sustainable manner. This study aims to determine the use of vermicompost and chemical fertilizers on the growth and yield of soybean plants. This study used a randomized block design (RBD) with vermicompost (V) and NPK (NPK) treatment, the treatment of which was: (P0) 750.0 kg ha-1 NPK, (P1) 562.5 kg ha-1 NPK + 30 ton ha-1 V, (P2) 375.0 kg ha-1 NPK + 30 tons ha-1 V, (P3) 187.5 kg ha-1 NPK + 30 tons ha-1 V and (P4) without chemical fertilizer + 30 tons of tonnes ha-1 V. Each treatment combination is repeated 3 times, so 15 experimental units are obtained. The results showed that administration of 30 tons ha-1 gave unreal results with other treatments for the growth and yield of Glycine max.